DISIPLIN PEGAWAI NEGERI SIPIL DI MASA PANDEMI COVID-19 - Mulyaningsih Mulyaningsih; Doni Rustanto (Jendela Inovasi Daerah, 2021)
Covid 19 Pandemic has changed the new practice of civil servants’ work system. It changed the work system from work from office to work from home, direct supervision to indirect supervision. This situation provokes further question of how the civil servants maintain their work performance and discipline. The objective of the study is to describe the practice of work performance and discipline during the implementation of work from home policy. For that purpose, we carried out a qualitative descriptive study and gathering the data by conducting interview, survey and observation. The findings showed that work discipline during the implementation of work from home policy were not optimally practiced, meanwhile the work performances were quiet good. In addition, this study indicated that the civil servants performances were more optimal during working from office. Thus we conclude that monitoring and evaluation are needed to enhance the work performance and discipline of civil servants in this situation.